Exploring the Writing Process of Multilingual Postsecondary Students - Troughton, Tessa E. (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
With an increasingly multilingual population made up of domestic and international students at Canadian universities, there is more to learn about the writing practices of multilingual students and the needs of multilingual postsecondary writers in a Canadian context. The purpose of this study was to learn in detail about the individual writing process of multilingual postsecondary students in a mid-sized university in eastern Canada. A qualitative methodology consisting of semi-structured interviews was followed. A small sample size of seven participants consisted of young adults enrolled at the postsecondary level who were recruited through posters on campus. The interviews were transcribed, coded holistically, and thematically analyzed using software. Findings reveal the individual writing process, use of strategies, and translingual practices in writing. Secondary findings highlight the impact of instructor feedback on learner attitudes and English language learners’ need for extra time to develop their academic English. These findings offer insights into the translingual writing process of multilingual postsecondary students.